Effects of the Medicare Part D comprehensive medication review on medication adherence among patients with Alzheimer's disease. (2nd September 2021) - Dong, Xiaobei; Tsang, Chi Chun Steve; Zhao, Shirong; Browning, Jamie A.; Wan, Jim Y.; Chisholm-Burns, Marie A.; Finch, Christopher K.; Tsao, Jack W.; Hines, Lisa E.; Wang, Junling
Abstract: Objective: Older patients with Alzheimer's disease (AD) are challenged with adhering to complex medication regimens. We examined effects of Comprehensive Medication Review (CMR), a required Medicare Part D Medication Therapy Management (MTM) program component, on medication adherence among AD patients. Methods: This retrospective study analyzed 100% of 2016–2017 Medicare claims covering the entire United States, linked to Area Health Resources Files. Medicare beneficiaries aged ≥65 years were included. Propensity score matching identified comparable intervention and comparison groups with the intervention defined as receiving a CMR in 2017. A difference-in-differences analysis included in multivariate logistic regressions an interaction term between CMR receipt and year 2017. The outcome measured was nonadherence to diabetes, hypertension and hyperlipidemia medications, with nonadherence defined as proportion of days covered <80% for study medications. Results: Unadjusted comparisons indicated the proportion of nonadherence for intervention group members decreased from 2016 to 2017 but increased for the comparison group. In adjusted analyses, reduction in medication nonadherence among the intervention group remained higher: odds ratios for the interaction term were 0.62 (95% confidence interval [CI] = 0.54–0.71), 0.54 (95% CI = 0.50–0.58) and 0.50 (95% CI = 0.47–0.53) respectively for diabetes, hypertension and hyperlipidemia medications. This suggests that the likelihood of nonadherence in the intervention group was respectively reduced by 38%, 46% and 50% more than the comparison group. Conclusions: CMR was found to reduce nonadherence to diabetes, hypertension and hyperlipidemia medications among older Medicare beneficiaries with AD. This provides evidence that the MTM program is effective for a population with unique medication compliance challenges.